Altered Resting-State Functional and White Matter Tract Connectivity in Stroke Patients With Dysphagia. (March 2014) - Li, Shasha; Ma, Zhenxing; Tu, Shipeng; Zhou, Muke; Chen, Sihan; Guo, Zhiwei; Gong, Qiyong; He, Li; Huang, Xiaoqi; Yao, Dezhong; Lui, Su; Yu, Bo; et al.
Background . Swallowing dysfunction is intractable after acute stroke. Our understanding of the alterations in neural networks of patients with neurogenic dysphagia is still developing. Objective . The aim was to investigate cerebral cortical functional connectivity and subcortical structural connectivity related to swallowing in unilateral hemispheric stroke patients with dysphagia. Methods . We combined a resting-state functional connectivity with a white matter tract connectivity approach, recording 12 hemispheric stroke patients with dysphagia, 12 hemispheric stroke patients without dysphagia, and 12 healthy controls. Comparisons of the patterns in swallowing-related functional connectivity maps between patient groups and control subjects included ( a ) seed-based functional connectivity maps calculated from the primary motor cortex (M1) and the supplementary motor area (SMA) to the entire brain, ( b ) a swallowing-related functional connectivity network calculated among 20 specific regions of interest (ROIs), and ( c ) structural connectivity described by the mean fractional anisotropy of fibers bound through the SMA and M1. Results . Stroke patients with dysphagia exhibited dysfunctional connectivity mainly in the sensorimotor-insula-putamen circuits based on seed-based analysis of the left and right M1 and SMA and decreased connectivity in the bilateral swallowing-related ROIs functional connectivity network. Additionally, white matter tract connectivity analysis revealed that the mean fractional anisotropy of the white matter tract was significantly reduced, especially in the left-to-right SMA and in the corticospinal tract. Conclusions . Our results indicate that dysphagia secondary to stroke is associated with disruptive functional and structural integrity in the large-scale brain networks involved in motor control, thus providing new insights into the neural remodeling associated with this disorder.